Phase change microcapsule, preparation method thereof and heat storage film

By mixing organic phase change materials with isocyanate compounds and amines or alcohols, phase change microcapsules with high thermal enthalpy value are prepared, which solves the problem of flow leakage of organic phase change materials during the phase change process and achieves high efficiency Heat storage film with heat storage effect.

CN119286474APending Publication Date: 2025-01-10CHINA LUCKY GROUP CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411213303.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing organic phase change materials are prone to flow and leakage during the phase change process, which makes it difficult for them to meet the heat storage effect requirements of different application scenarios during use.

Method used

Using a method of preparing phase change microcapsules, organic phase change materials are mixed with isocyanate compounds and amines or alcohols, and shell materials are formed by heating treatment of oil and water emulsions to provide adhesion and heat storage film. The heat storage function with high thermal enthalpy value is achieved without adding adhesive.

Benefits of technology

The high thermal enthalpy value and good adhesion of phase-change microcapsules are achieved, the heat storage performance and stability of the heat storage film are improved, and the heat storage effect of the adhesive is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119286474A_ABST
    Figure CN119286474A_ABST
Patent Text Reader

Abstract

The invention discloses a phase change microcapsule and a preparation method thereof and a heat storage film, and the method for preparing the phase change microcapsule comprises the following steps: mixing an organic phase change material with an isocyanate compound to obtain an oil phase solution; mixing a dispersing agent with water to obtain a water-phase solution; mixing the oil-phase solution with the water-phase solution, and carrying out heating treatment to obtain an oil-water emulsion; the oil-water emulsion is mixed with an amine substance and / or an alcohol substance, heating treatment is carried out, the phase change microcapsule is obtained, the amine substance comprises at least one of an amine oligomer and an amine monomer, and the alcohol substance comprises an alcohol oligomer. According to the method, an adhesive does not need to be added, and the heat storage film has a relatively high enthalpy value while relatively high adhesion is achieved between the heat storage layer and the base film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of phase change heat storage materials, and in particular, to phase change microcapsules and a preparation method thereof, and a heat storage film containing the phase change microcapsules. Background Art

[0002] Organic phase change materials are substances with heat storage and temperature regulation functions, and have great application potential in the fields of textiles, aerospace, construction, energy storage, transportation, and electronic products. Phase change materials can be mainly divided into two categories: organic and inorganic. Among them, organic phase change materials have the advantages of not easy to phase separation, low corrosiveness and stable performance, and have received close attention from the engineering community. However, due to the transition from solid phase to liquid phase in the phase change process of organic phase change materials, it is prone to flow, leakage and other problems during use. Therefore, organic phase change materials usually need to be encapsulated or coated, for example, in the form of phase change microcapsules. In order to meet different application scenarios and usage conditions, organic phase change materials need to be combined with effective packaging methods and provide sufficient heat storage effects, which places high demands on material design and material properties. Therefore, the current phase change microcapsules still need to be further improved. Summary of the invention

[0003] In the first aspect of the present application, the present application proposes a method for preparing phase change microcapsules, comprising: mixing an organic phase change material with an isocyanate compound to obtain an oil phase solution; mixing a dispersant with water to obtain an aqueous phase solution; mixing the oil phase solution with the aqueous phase solution, and heating the mixture to obtain an oil-water emulsion; mixing the oil-water emulsion with an amine substance and / or an alcohol substance, and heating the mixture to obtain the phase change microcapsules, wherein the amine substance includes at least one of an amine oligomer and an amine monomer, and the alcohol substance includes an alcohol oligomer.

[0004] The phase-change microcapsules manufactured by the phase-change microcapsule preparation method proposed in the present invention can wrap the organic phase-change material as the core material in the shell material formed by the reaction. The shell material surface of the phase-change microcapsules has a large number of hydroxyl groups or amino groups, which can provide surface adhesion to the phase-change microcapsules. The adhesion of the phase-change microcapsules makes the phase-change microcapsule suspension used for coating the base film self-adhesive when preparing the heat storage film, and the production process does not need to add adhesives. While the heat storage layer and the base film have strong adhesion, the heat storage film has a higher enthalpy value.

[0005] In some embodiments, the total addition amount of the amine substances and alcohol substances is 2 parts by weight to 10 parts by weight, wherein the amine oligomers include at least one of polyetheramine, polyethyleneimine and its derivatives, polypropyleneamine, polyethyleneamine and its derivatives, polypropyleneamine and its derivatives, poly-L-lysine, and poly-L-ornithine, and the weight average molecular weight of the amine oligomers is less than or equal to 500; and / or, the amine monomers include at least one of diethanolamine, triethanolamine, diethylenetriamine, tetraethylenepentamine, and pentaethylenehexamine; and / or, the alcohol oligomers include at least one of polyester polyols, polyether polyols, and polyvinyl alcohol, and the number average molecular weight of the alcohol oligomers is less than or equal to 600.

[0006] During the preparation of phase change microcapsules, a certain amount of amines and alcohols, such as oligomers and / or polymer monomers, are added. The oligomers and / or polymer monomers can react better with the oil-water emulsion during the preparation process, making the reaction control easier.

[0007] In some embodiments, the isocyanate compound includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and xylylene diisocyanate; and / or, the added amount of the isocyanate compound is 2 parts by weight to 8 parts by weight.

[0008] In the process of preparing phase-change microcapsules, a certain amount of isocyanate compounds are added and mixed with the organic phase-change material to obtain an oil phase solution that is stable at room temperature.

[0009] In some embodiments, the organic phase change material includes at least one of stearic acid, lauric acid, palmitic acid, myristic acid, n-octadecane, n-nonadecane, n-eicosane, n-heneicosane, n-docosane, n-tricosane, n-tetracosane, n-pentacosane, n-hexacosane, n-heptacosane, n-octacosane, n-nonacosane, and n-triacontan; and / or, the organic phase change material is added in an amount of 10 to 50 parts by weight.

[0010] During the preparation of phase change microcapsules, a certain amount of organic phase change material is added. The organic phase change material is wrapped in the shell material in the prepared phase change microcapsules. After the preparation process of the phase change microcapsules, its properties can remain stable and the phase change heat storage function can be exerted.

[0011] In some embodiments, the dispersant includes at least one of glyceryl monostearate, glyceryl tristearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, Span 60, Span 80, Tween 80, and alkylphenol polyoxyethylene ether; and / or, the amount of the dispersant added is 0.1 parts by weight to 2 parts by weight; and / or, the amount of water added is 30 parts by weight to 80 parts by weight.

[0012] A certain amount of dispersant is added and mixed with water to obtain an aqueous phase solution, and an oil-water emulsion can be obtained by mixing the water-oil two-phase solution, thereby improving the dispersibility of the organic phase change material in the oil-water emulsion.

[0013] In some embodiments, the dispersant includes an aqueous dispersant and an oily dispersant, the aqueous dispersant includes sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and Tween 80, the oily dispersant includes glyceryl monostearate, glyceryl tristearate, Span 60, Span 80, and alkylphenol polyoxyethylene ether, and the mass ratio of the aqueous dispersant to the oily dispersant is (0.25-1.5):1.

[0014] During the preparation of phase change microcapsules, a certain amount of dispersant is added, and the dispersant is a mixture of an oily dispersant and an aqueous dispersant, so that the mixed oil-water emulsion contains an appropriate amount of hydrophilic groups and lipophilic groups, thereby improving the dispersion uniformity of the oil-water emulsion.

[0015] In a second aspect of the present application, the present application proposes a phase change microcapsule, which is prepared by the method for preparing phase change microcapsule proposed in the present application.

[0016] The phase change microcapsules proposed in the present application have a relatively low shell material mass ratio, so that the overall enthalpy value is closer to the enthalpy value of the organic phase change material itself, and the heat storage capacity is better.

[0017] In some embodiments, it comprises a core and a shell encapsulating the core, the core comprises an organic phase change material, the shell comprises polyurea and / or polyurethane, and the mass proportion of the organic phase change material in the phase change microcapsule is 70%-90%.

[0018] The phase change microcapsule proposed in this application has a shell including polyurea and / or polyurethane, and a phase change microcapsule suspension is prepared in the process of manufacturing the heat storage film. The shell material of the phase change microcapsule has adhesion. The shell material has a low mass ratio while meeting a certain strength requirement, which helps to improve the phase change heat storage performance of the phase change microcapsule.

[0019] In a third aspect of the present application, the present application proposes a heat storage film, comprising a first base film and a heat storage layer located on one side of the first base film, wherein the heat storage layer comprises phase change microcapsules prepared by the method for preparing phase change microcapsules proposed in the present application.

[0020] By utilizing the adhesion of the shell material of the phase change microcapsule itself, the phase change microcapsule can be well fixed on the surface of the base film without adding any adhesive, and the heat storage film has a better heat storage function.

[0021] In some embodiments, a second base film is provided on the side of the heat storage layer away from the first base film, and a composite adhesive layer is provided on the side of the second base film facing the heat storage layer; the composite adhesive layer includes at least one of alkyd resin, polyurethane, polyester polyol, polyacrylate, styrene butadiene latex, carboxylated styrene butadiene latex and polyvinyl alcohol. The heat storage film proposed in this application can provide better protection for the heat storage layer by adding a second base film, improve the overall mechanical properties of the heat storage film, and assist in increasing the thickness of the heat storage layer, which is suitable for more usage scenarios. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0023] Figure 1 This is a scanning electron microscope image of the phase change microcapsule in Example 1 of the present application. DETAILED DESCRIPTION

[0024] The embodiments of the present application are described in detail below. Examples of the embodiments are shown in the drawings, but unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of actually identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0025] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0026] The terms "including" and "having" in the specification and claims of the present application and any modifications thereof are open expressions, that is, including the contents specified in the present application but not excluding other contents.

[0027] In the description of this application, regardless of whether the words "about" or "approximately" are used, all the numbers disclosed herein are approximate values. The value of each number may differ by less than 10% or a reasonable difference considered by those skilled in the art, such as 1%, 2%, 3%, 4% or 5%.

[0028] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0029] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0030] Phase-change microencapsulation of organic phase change materials, that is, wrapping the organic phase change materials as core materials in dense shell materials, can effectively solve the problem of leakage of organic phase change materials. Phase change microcapsules wrapped with organic phase change materials need to be set on the surface of the base film to form a heat storage film layer as a component of the heat storage function in the heat storage film, thereby playing the role of phase change heat storage. When the phase change microcapsules are used in the heat storage film, when the phase change microcapsules are set on the surface of the base film, the phase change microcapsules need to be mixed with an adhesive to prepare a slurry, and then the phase change microcapsules made into a slurry are coated on the base film using the adhesion provided by the adhesive to make a heat storage film that meets the functional requirements. Although the adhesive provides adhesion, it itself cannot be used for phase change heat storage, which will reduce the heat storage enthalpy value per unit weight of the heat storage film, thereby reducing the thermal enthalpy density of the heat storage film and affecting the heat storage effect.

[0031] In the first aspect of the present application, the present application proposes a method for preparing phase change microcapsules, so that phase change microcapsules with higher thermal enthalpy values ​​can be prepared by a simple method. Specifically, the method for preparing phase change microcapsules includes:

[0032] S100: Mixing organic phase change materials with isocyanate compounds

[0033] In some embodiments, in this step, the organic phase change material is mixed with an isocyanate compound to obtain an oil phase solution. At room temperature, the solid organic phase change material needs to be dispersed by a liquid. Thus, by mixing the organic phase change material with the isocyanate compound, the organic phase change material can be dispersed, and at the same time, the surface of the organic phase change material is formed into a partial reactant for the polymerization reaction to form a shell material.

[0034] In some embodiments, the isocyanate compound includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate, and xylylene diisocyanate.

[0035] In the process of preparing phase change microcapsules, a certain amount of isocyanate compounds are added and mixed with organic phase change materials to obtain an oil phase solution.

[0036] In some embodiments, the isocyanate compound is added in an amount of 2 parts by weight to 8 parts by weight.

[0037] The amount of isocyanate compound added is controlled so that it can fully wrap the organic phase change material. When the amount of isocyanate compound added is within the aforementioned range, excessive addition of isocyanate compound helps the shell material wall thickness of the phase change microcapsule formed later to be moderate, high in strength, and can fully wrap the organic phase change material. Furthermore, the appropriate addition of isocyanate compound can control the shell material to have a large amount of amino and / or hydroxyl groups remaining on the surface after formation, providing adhesion to the surface of the phase change microcapsule, which is beneficial to the adhesion between the phase change microcapsule and the base film.

[0038] In some embodiments, the organic phase change material includes at least one of stearic acid, lauric acid, palmitic acid, myristic acid, n-octadecane, n-nonadecane, n-eicosane, n-heneicosane, n-docosane, n-tricosane, n-tetracosane, n-pentacosane, n-hexacosane, n-heptacosane, n-octacosane, n-nonacosane, and n-triacontane.

[0039] The aforementioned organic phase change material is selected for its low cost, good stability, non-corrosiveness and no supercooling and phase separation phenomenon.

[0040] In some embodiments, the organic phase change material is added in an amount of 10 parts by weight to 50 parts by weight.

[0041] The amount of the organic phase change material added is controlled, and the amount of the organic phase change material added, the amount of the isocyanate compound added, and the amount of the added amine substance and / or alcohol substance added are controlled at the same time, so that the mass ratio of the prepared phase change microcapsule shell material is low and the shell material is fully wrapped.

[0042] S200: Mix dispersant with water

[0043] In some embodiments, the dispersant is mixed with water in this step to obtain an aqueous solution. After the dispersant is mixed with water, the dispersant is distributed more evenly in the aqueous solution. When the aqueous solution is subsequently mixed with the oil solution, an oil-water emulsion with a more even solute dispersion can be formed, which is beneficial for the dispersant to play a stabilizing role at the water-oil interface, reduce excessive adhesion and aggregation between organic phase change materials, and make the prepared phase change microcapsule particles more uniform. The suspension made of the phase change microcapsules is also more likely to form a heat storage layer with a more even distribution of microcapsules and a more uniform thickness when applied to a substrate.

[0044] In some embodiments, the dispersant includes at least one of glyceryl monostearate, glyceryl tristearate, sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, SPAN 60, SPAN 80, TWEEN 80, and alkylphenol polyoxyethylene ether.

[0045] In some embodiments, the dispersant is added in an amount of 0.1 parts by weight to 2 parts by weight.

[0046] In some embodiments, the amount of water added is 30 parts by weight to 80 parts by weight.

[0047] In the process of preparing phase change microcapsules, a certain amount of dispersant is added and mixed with water to obtain an aqueous solution. When the aqueous solution is mixed with the oil solution, the dispersant enters the oil-water interface and effectively reduces the interfacial energy, so that the dispersion obtained by mechanical shear force during emulsification remains relatively stable in the oil-water emulsion, reducing re-aggregation after the dispersion operation, thereby controlling the particle size of the dispersion to be stable, so that the size of the phase change microcapsules finally prepared is relatively consistent and its heat storage function is stable.

[0048] In some embodiments, the dispersant includes an aqueous dispersant and an oily dispersant, the aqueous dispersant includes sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and Tween 80, the oily dispersant includes glyceryl monostearate, glyceryl tristearate, Span 60, Span 80, and alkylphenol polyoxyethylene ether, and the mass ratio of the aqueous dispersant to the oily dispersant is (0.25-1.5):1.

[0049] By mixing the oily dispersant with the aqueous dispersant, the relative strength of the hydrophobic group and the hydrophilic group brought by the added dispersant is within a suitable range, and its HLB value (hydrophile-lipophile balance) is within the range of 10-20. At this time, the hydrophobic group and the hydrophilic group reach a relative balance, which is conducive to maintaining the stability of the dispersion in the oil-water emulsion, promoting full dispersion, and helping the size of the prepared phase change microcapsules to be more uniform. Moreover, no additional organic solvent is required in the manufacturing process of the phase change microcapsules, which is environmentally friendly.

[0050] S300: Mixing the oil phase solution with the water phase solution and performing a heating treatment

[0051] In some embodiments, in this step, the oil phase solution is mixed with the water phase solution and subjected to a heating treatment to obtain an oil-water emulsion.

[0052] In some embodiments, after the aqueous phase solution is heated and stirred at 50° C. to 80° C., the oil phase is poured into the aqueous phase solution at a stirring speed of 500 rpm-2000 rpm and stirred for emulsification for 5-20 minutes to form an oil-water emulsion.

[0053] Mechanical stirring is added when the aqueous phase solution and the oil phase solution are mixed. Shear force is introduced into the mixing of the aqueous phase solution and the oil phase solution through mechanical stirring, and a dispersion with uniform particle size in the oil-water emulsion is obtained through mechanical shear force dispersion.

[0054] In some embodiments, the method further comprises: performing a shear dispersion treatment on the oil-water emulsion to obtain an oil-water emulsion with uniform particle size.

[0055] In some embodiments, the oil-water emulsion is sheared for 5-20 minutes at a shear rate of 3000 rpm-10000 rpm by a high-speed shearing device to form an oil-water emulsion with a uniform dispersed phase particle size.

[0056] After obtaining the oil-water emulsion, the dispersed phase in the oil-water emulsion is further sheared and dispersed by a high-speed shearing device, and at the same time, the effective arrangement of the dispersant in the oil-water emulsion is further promoted, which is conducive to obtaining an oil-water emulsion with a uniform dispersed phase particle size.

[0057] S400: Mixing the oil-water emulsion with amine substances and / or alcohol substances and performing a heating treatment

[0058] In some embodiments, in this step, the oil-water emulsion is mixed with an amine substance and / or an alcohol substance and subjected to a heat treatment to obtain the phase change microcapsule, wherein the amine substance includes at least one of an amine oligomer and an amine monomer, and the alcohol substance includes an alcohol oligomer.

[0059] After the oil-water emulsion is mixed with amines and / or alcohols, the amines and / or alcohols will undergo a polymerization reaction with the isocyanate compounds in the oil-water emulsion to produce the shell material of the phase-change microcapsule. A large number of unreacted hydroxyl groups and amino groups remain on the surface of the shell material, providing adhesion of the phase-change microcapsule shell material. The surface adhesion of the phase-change microcapsule shell material is conducive to the subsequent preparation of the heat storage film, in which the phase-change microcapsules can be directly formed on the surface of the base film in a simple manner without adding adhesives. Since no adhesive is added, the weight proportion of the organic phase change material in the heat storage layer is relatively high, and the heat storage performance is better.

[0060] In some embodiments, the amine oligomer includes at least one of polyetheramine, polyethyleneimine and its derivatives, polypropyleneamine, polyethyleneamine and its derivatives, polypropyleneamine and its derivatives, poly-L-lysine, and poly-L-ornithine, and the weight average molecular weight of the amine oligomer is less than or equal to 500.

[0061] In order to form a shell material wall with relatively uniform thickness, the molecular weight of the added amine substance cannot be too high; but at the same time, in order to achieve sufficient encapsulation of the organic phase change material by the shell material, the use of monomers with higher molecular weight or branched oligomers can make the formed shell material structure more compact and improve the heat storage performance.

[0062] In some embodiments, the amine monomer includes at least one of diethanolamine, triethanolamine, diethylenetriamine, tetraethylenepentamine, and pentaethylenehexamine.

[0063] In some embodiments, the alcohol oligomer includes at least one of polyester polyol, polyether polyol, and polyvinyl alcohol, and the number average molecular weight of the alcohol oligomer is less than or equal to 600.

[0064] In order to form a shell material wall with relatively uniform thickness, the molecular weight of the added alcohol oligomer cannot be too high; but at the same time, in order to achieve sufficient encapsulation of the organic phase change material by the shell material, the use of monomers with higher molecular weight or branched oligomers can make the formed shell material structure more compact and improve the heat storage performance.

[0065] Amines and / or alcohols are added to the oil-water mixture, and the total amount of the amines and alcohols added is controlled. The added amines and / or alcohols react with the isocyanate compounds encapsulating the organic phase change material in the oil-water emulsion to form a shell material.

[0066] In some embodiments, the total amount of the amine substance and the alcohol substance added is 2 parts by weight to 10 parts by weight.

[0067] When the total addition amount of the amine substances and alcohol substances is within the aforementioned range, the wall thickness of the formed shell material is moderate, the mass of the shell material accounts for a relatively large proportion of the total mass of the phase change microcapsule, the mass of the organic phase change material accounts for a relatively high proportion, and the heat storage function of the heat storage film is better.

[0068] In some embodiments, an oil-water emulsion is placed in an emulsifying pot, the stirring speed of the emulsifying pot is set to 200rpm-800rpm, the temperature of the emulsifying pot is set to 50°C-80°C, amine substances and / or alcohol substances are added, and the reaction is carried out for 2 hours to 6 hours to prepare phase change microcapsules.

[0069] Amines and / or alcohols are added to the oil-water mixture prepared in the previous step, and appropriate temperature conditions for the polymerization reaction are provided to promote the polymerization reaction of the amines and / or alcohols with the isocyanate compounds at a mild reaction rate. Stirring is added to reduce the aggregation of phase change microcapsules formed during the coating and maturation process, which is conducive to the formation of phase change microcapsules with more uniform particle sizes.

[0070] In a second aspect of the present application, the present application proposes a phase change microcapsule, which is prepared by the method for preparing phase change microcapsule proposed in the present application.

[0071] The mass proportion of the shell material of the phase change microcapsule is relatively low, the particle size of the phase change microcapsule is relatively uniform, the overall thermal enthalpy value is closer to the thermal enthalpy value of the organic phase change material itself, and the heat storage capacity is better.

[0072] In some embodiments, the phase change microcapsule includes a core and a shell encapsulating the core, the core includes an organic phase change material, the shell includes polyurea and / or polyurethane, and the mass proportion of the organic phase change material in the phase change microcapsule is 70%-90%.

[0073] The shell of the phase change microcapsule proposed in the present application includes polyurea and / or polyurethane. The polyurea and polyurethane materials have good oil resistance and heat resistance, which helps the microcapsule to maintain stable material properties in a wide temperature range, resist aging, and be non-flammable at high temperatures. At the same time, because the raw materials amine substances and / or alcohol substances for the synthesis of polyurea and / or polyurethane polymerization reactions contain a large number of amino groups and / or hydroxyl groups, a large number of uncross-linked amino groups and / or hydroxyl groups can be retained by controlling the degree of polymerization reaction, thereby providing surface adhesion for the phase change microcapsule. In the production process of further making a heat storage film, the adhesive can be omitted, and the obtained heat storage film has a higher thermal enthalpy value and a good phase change heat storage function.

[0074] In the third aspect of the present application, the present application proposes a heat storage film, including a first base film and a heat storage layer located on one side of the first base film, wherein the heat storage layer includes phase change microcapsules prepared by the method for preparing phase change microcapsules proposed in the present application. By utilizing the adhesion of the shell material of the phase change microcapsules proposed in the present application, no additional adhesive is required to be added to the heat storage layer. During the roll production process, a smaller shaft diameter can be used to achieve a higher heat storage capacity, and the heat storage film has a higher heat storage density. In addition, the size of the phase change microcapsules is relatively uniform, and the heat storage capacity per unit area of ​​the heat storage film is more uniform. When in use, the product effect is stable and easy for users to operate.

[0075] In some embodiments, a second base film is provided on the side of the heat storage layer away from the first base film, and a composite adhesive layer is provided on the side of the second base film facing the heat storage layer; the composite adhesive layer includes at least one of alkyd resin, polyurethane, polyester polyol, polyacrylate, styrene butadiene latex, carboxy styrene butadiene latex and polyvinyl alcohol.

[0076] By setting a second base film on the side of the heat storage film away from the first base film, the material of the second base film can be adjusted according to the applicable occasion, so that the application range of the heat storage film is wider. At the same time, the second base film can play a role in packaging and protecting the heat storage layer, improving the overall mechanical properties of the heat storage film; in addition, the surface constraint provided by the second base film allows the thickness of the heat storage layer to be thicker, increasing the overall thermal enthalpy value of the heat storage film, improving the heat storage function, and being suitable for more usage scenarios.

[0077] The present application proposes a method for preparing a heat storage film, which is simple in process and easy to operate to prepare a heat storage film with a high thermal enthalpy value. Specifically, the method for preparing the heat storage film includes:

[0078] S1: Prepare phase change microcapsules, curing agent and leveling agent to form a phase change microcapsule suspension

[0079] In some embodiments, the weight proportion of the phase change microcapsules in the phase change microcapsule suspension is 20%-60%, and the weight proportion of the curing agent in the phase change microcapsule suspension is 0.2%-1%. The raw materials used in the preparation of the phase change microcapsule suspension are easily available, the process is simple, and it is suitable for industrial production.

[0080] S2: coating the phase change microcapsule suspension on the first base film to form a heat storage layer to obtain a heat storage film.

[0081] In some embodiments, the coating method may be a comma blade or a slot coating.

[0082] In some embodiments, the first base film is a polyester film.

[0083] The first base film is made of polyester film, which has the advantages of low hygroscopicity, fatigue resistance, solvent resistance, and maintaining mechanical properties at high temperatures.

[0084] In some embodiments, the enthalpy value of the heat storage layer is greater than 180 J / g, and the peel strength between the heat storage layer and the first base film is greater than or equal to 1 N / 13 mm.

[0085] The peeling strength of the heat storage layer is high, the heat storage layer is firmly combined with the first base film and is not easy to fall off, and the structure of the composite film is stable.

[0086] S3: Apply the composite adhesive on the second base film

[0087] In some embodiments, the composite adhesive includes at least one of alkyd resin, polyurethane, polyester polyol, polyacrylate, styrene butadiene latex, carboxylated styrene butadiene latex, and polyvinyl alcohol.

[0088] S4: Compounding the second base film coated with the composite adhesive with the heat storage film

[0089] In some embodiments, the compounding conditions are a temperature of 50° C.-80° C. and a pressure of 0.2 MPa-0.8 MPa.

[0090] The composite adhesive provides adhesion to the surface of the second base film, so that the second base film coated with the composite adhesive can be covered on the surface of the heat storage layer, providing surface protection for the heat storage layer and improving the mechanical properties of the heat storage film.

[0091] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0092] Example 1

[0093] (1) Preparation of oil phase: Stearic acid is selected as the organic phase change material and diphenylmethane diisocyanate is selected as the isocyanate compound. Weigh 10g of stearic acid and heat it to 80°C to melt it. Then add 1g of diphenylmethane diisocyanate and stir evenly to obtain an oil phase solution containing the organic phase change material. The oil phase solution of the organic phase change material is kept warm at 80°C for later use.

[0094] (2) Preparation of aqueous phase: Monoglyceride and SPAN 80 were selected as dispersants. 30 g of pure water, 0.05 g of glycerol monostearate and 0.05 g of SPAN 80 were weighed and mixed evenly to obtain an aqueous phase solution.

[0095] (3) Emulsification: After the aqueous phase solution is heated and stirred in a water bath at 80°C, the oil phase solution is poured into the aqueous phase solution at a stirring speed of 500 rpm and stirred for emulsification for 5 minutes to obtain an oil-water emulsion.

[0096] (4) Shear dispersion: The formed oil-water emulsion was sheared at 3000 rpm for 10 minutes using a high-speed shearing device to form an oil-water emulsion with uniform particle size.

[0097] (5) Coating and maturation: Polyetheramine (product number ED230) was selected as the amine substance and / or alcohol substance. The oil-water emulsion was placed in an emulsification pot, the stirring speed of the emulsification pot was 200 rpm, the temperature of the emulsification pot was set to 50°C, 1 g of polyetheramine ED230 was added, and the reaction was carried out for 6 hours to generate a self-adhesive phase change microcapsule suspension.

[0098] Example 2

[0099] Example 2 is consistent with Example 1, except that xylene diisocyanate is selected as the isocyanate compound and polypropylene glycol PPG-400 (polyether polyol) is selected as the alcohol substance.

[0100] Example 3

[0101] Example 3 is consistent with Example 1, except that xylylene diisocyanate is selected as the isocyanate compound and pentaethylenehexamine is selected as the amine substance.

[0102] Example 4

[0103] Example 4 is consistent with Example 1, except that toluene diisocyanate is selected as the isocyanate compound and pentaethylenehexamine is selected as the amine substance.

[0104] Example 5

[0105] Example 5 is consistent with Example 1, except that glyceryl tristearate and sodium lauryl sulfate are selected as dispersants, and the dispersant is 0.01 g of glyceryl tristearate and 0.05 g of sodium lauryl sulfate.

[0106] Example 6

[0107] Example 6 is consistent with Example 1, except that the phase change material selected is n-tetracosane.

[0108] Comparative Example 1

[0109] Preparation of urea-formaldehyde prepolymer:

[0110] Weigh 5 g of urea, 40 g of water, and 14 g of formaldehyde, add triethanolamine to adjust the pH to 8, and react at 70° C. for 1 hour under stirring at 300 rpm to form a urea-formaldehyde prepolymer.

[0111] Preparation of phase change microcapsules:

[0112] Weigh 40g of n-eicosane, heat to 60°C until it melts to form liquid n-eicosane; weigh 200g of pure water, 0.8g of Span 80, and 0.2g of Tween 80, place them in a 60°C water bath and stir them evenly at 400rpm, then pour in liquid n-eicosane, disperse them at 900rpm for 10min, and slowly drip urea-formaldehyde prepolymer to form phase change microcapsules, the shell of which is polyurea-formaldehyde.

[0113] Comparative Example 2

[0114] Preparation of melamine prepolymer:

[0115] Weigh 18 g of melamine, 35 g of formaldehyde and 35 g of pure water, and react at 75° C. for 1.5 hours with an overhead stirring device at 300 rpm to form a melamine prepolymer.

[0116] Preparation of phase change microcapsules:

[0117] Weigh 80g of n-octadecane, heat to 60°C until it melts to form liquid n-octadecane; weigh 200g of pure water, 0.8g of sodium dodecylbenzene sulfonate, and 0.2g of Span 80, place them in a 60°C water bath and stir them evenly at 400rpm, then pour in liquid n-eicosane, disperse them at 900rpm for 10min, and slowly drip melamine prepolymer to form phase change microcapsules, the shell of which is polymelamine.

[0118] The microcapsules in the above-mentioned embodiments and comparative examples are used to prepare a heat storage film, and the specific steps include:

[0119] (1) 99 wt % of phase change microcapsules, 0.5 wt % of curing agent, and 0.5 wt % of leveling agent were prepared into a slurry, which was coated on a polyester film (first base film) by a comma scraper to form a film A.

[0120] (2) Polyacrylate is selected as the composite adhesive, and the composite adhesive is coated on another polyester film (second base film) to form film B.

[0121] (3) Film A and film B are compounded under the conditions of 70°C and 0.5 MPa to form a heat storage film.

[0122] The microcapsule suspensions and heat storage films in the aforementioned embodiments and comparative examples were subjected to the following tests. The test results are shown in Table 1.

[0123] Enthalpy test: refer to standard GB / T 19077.1-2003 Plastics, differential scanning calorimetry (DSC).

[0124] (1) Sample preparation: Take a certain amount of microcapsule emulsion, treat and dry it as a test sample.

[0125] (2) Temperature and flow control: 20℃-30℃, N2 as protective gas. The protective gas output pressure is 0.03Mpa, and the flow rate is constant. When testing samples, the sample flow rate is 20mL / min, and when in standby mode, the sample flow rate is 10mL / min. After starting up, first adjust the output pressure and flow rate of the protective gas and purge gas and wait for them to stabilize. Whenever the sample holder is replaced (such as: TG-DSC is replaced with TG-DTA or vice versa) or the crucible type is changed due to test needs, the instrument settings must be modified to match the working conditions of the instrument.

[0126] (3) Sample weighing: Use a balance with an accuracy of 0.01 mg or more and perform triple baseline calibration.

[0127] (4) Measurement and operation program: Select New in the File menu to enter the programming file. Select the Correction measurement mode, enter the identification number, and the sample name can be left blank (Empty), no weighing is required. Click Continue. Select the standard temperature correction file and open it. Select the standard sensitivity correction file and open it. Now enter the temperature control programming program. The instrument starts measuring until it is completed.

[0128] Peeling force test: the heat storage film is cut into 25cm wide and 20cm long sample strips to be tested, 3M double-sided tape is pasted on the surface of the second base film away from the heat storage layer, and the sample strip to be tested is adhered to a hard substrate with the same width as the sample strip and not easy to deform by 3M double-sided tape, and the adhesion length is 10cm. The 103B electronic tensile testing machine designed and manufactured by Shenzhen Vanke Testing Equipment Co., Ltd. is used to fix the end of the hard substrate without the heat storage film adhered to the lower fixture, and the end of the heat storage film without the hard substrate adhered to the upper fixture. At this time, the heat storage film and the hard substrate form an angle of 180°, start the measurement program, and measure three times in parallel and take the average value as the required result.

[0129] Storage stability test of phase change microcapsules: After being stored for 15 days, the particle size was tested respectively, and the difference in particle size before and after 15 days was recorded as △D50.

[0130] Table 1

[0131]

[0132]

[0133] Figure 1 This is a scanning electron microscope image of the phase change microcapsule in Example 1. As can be seen from the image, the shell material of the phase change microcapsule covers the organic phase change material more completely, and the particle size is relatively uniform.

[0134] It can be seen from Table 1 that when the particle size D50 is similar, the enthalpy value of the phase change microcapsule is higher, indicating that the mass proportion of the organic phase change material in the phase change microcapsule is relatively large, and the heat storage performance is better. The shell material of the phase change microcapsule itself has good adhesion, and the phase change microcapsule can be well fixed on the surface of the base film without the addition of an adhesive, so the prepared heat storage film has a large peeling force test value. However, the adhesion between the shell material of the phase change microcapsule and the substrate in Comparative Examples 1 and 2 is poor, and delamination is prone to occur. In Examples 1-6, the △D50 value of the phase change microcapsule is smaller than the △D50 value in Comparative Examples 1-2, indicating that the phase change microcapsule of the present application has better storage stability.

[0135] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0136] In the description of the present application, “plurality” means two or more.

[0137] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0138] In the present application, the writing order of each step does not mean a strict execution order and does not constitute any limitation on the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0139] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing phase change microcapsules, characterized in that: include: mixing an organic phase change material with an isocyanate compound to obtain an oil phase solution; mixing the dispersant with water to obtain an aqueous solution; The oil phase solution is mixed with the water phase solution, and subjected to a heating treatment to obtain an oil-water emulsion; The oil-water emulsion is mixed with an amine substance and / or an alcohol substance, and subjected to a heat treatment to obtain the phase-change microcapsule, wherein the amine substance includes at least one of an amine oligomer and an amine monomer, and the alcohol substance includes an alcohol oligomer.

2. The method according to claim 1, characterized in that The total amount of the amine substance and the alcohol substance added is 2 parts by weight to 10 parts by weight, wherein: The amine oligomer includes at least one of polyetheramine, polyethyleneimine and its derivatives, polypropyleneamine, polyvinylamine and its derivatives, polypropyleneamine and its derivatives, poly-L-lysine, and poly-L-ornithine, and the weight average molecular weight of the amine oligomer is less than or equal to 500; and / or, The amine monomer includes at least one of diethanolamine, triethanolamine, diethylenetriamine, tetraethylenepentamine and pentaethylenehexamine; and / or, The alcohol oligomer includes at least one of polyester polyol, polyether polyol and polyvinyl alcohol, and the number average molecular weight of the alcohol oligomer is less than or equal to 600.

3. The method according to claim 2, characterized in that The isocyanate compound includes at least one of diphenylmethane diisocyanate, toluene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, 4,4-dicyclohexylmethane diisocyanate and xylylene diisocyanate; and / or, The added amount of the isocyanate compound is 2 parts by weight to 8 parts by weight.

4. The method according to any one of claims 1 to 3, characterized in that: The organic phase change material comprises at least one of stearic acid, lauric acid, palmitic acid, myristic acid, n-octadecane, n-nonadecane, n-eicosane, n-heneicosane, n-docosane, n-tricosane, n-tetracosane, n-pentacosane, n-hexacosane, n-heptacosane, n-octacosane, n-nonacosane, and n-triacontane; and / or, The organic phase change material is added in an amount of 10 parts by weight to 50 parts by weight.

5. The method according to any one of claims 1 to 3, characterized in that: The dispersant comprises at least one of glyceryl monostearate, glyceryl tristearate, sodium dodecyl sulfonate, sodium dodecylbenzene sulfonate, Span 60, Span 80, Tween 80, and alkylphenol polyoxyethylene ether; and / or, The amount of the dispersant added is 0.1 parts by weight to 2 parts by weight; and / or, The amount of water added is 30 parts by weight to 80 parts by weight.

6. The method according to claim 5, characterized in that The dispersant includes an aqueous dispersant and an oily dispersant, the aqueous dispersant includes at least one of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, and Tween 80, the oily dispersant includes at least one of monostearate glyceryl, tristearate glyceryl, Span 60, Span 80, and alkylphenol polyoxyethylene ether, and the mass ratio of the aqueous dispersant to the oily dispersant is (0.25-1.5):

1.

7. A phase change microcapsule, characterized in that: The method is prepared by any one of claims 1 to 6.

8. The phase-change microcapsule according to claim 7, characterized in that: It comprises an inner core and a shell which wraps the inner core, wherein the inner core comprises an organic phase change material, the shell comprises polyurea and / or polyurethane, and the mass proportion of the organic phase change material in the phase change microcapsule is 70%-90%.

9. A heat storage film, characterized in that: It comprises a first base film and a heat storage layer located on one side of the first base film, wherein the heat storage layer comprises the phase change microcapsule according to claim 7 or 8.

10. The heat storage film according to claim 9, characterized in that: A second base film is provided on a side of the heat storage layer away from the first base film, and a composite adhesive layer is provided on a side of the second base film facing the heat storage layer; The composite adhesive layer includes at least one of alkyd resin, polyurethane, polyester polyol, polyacrylate, styrene butadiene latex, carboxylated styrene butadiene latex and polyvinyl alcohol.